2004
DOI: 10.1002/pola.20472
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethyleneimine)/arginine–glycine–aspartic acid conjugates prepared with N‐succinimidyl 3‐(2‐pyridyldithio)propionate: An investigation of peptide coupling and conjugate stability

Abstract: Poly(ethylene imine) (PEI), a highly cationic polymer, is being used for deoxyribonucleic acid (DNA) complexation and delivery into cells. To enhance the cellular uptake of polymer/DNA complexes, arginine-glycine-aspartic acid (RGD) peptides have been conjugated to PEI with N-succinimidyl 3-(2-pyridyldithio)propionate (SPDP). This coupling scheme creates a disulfide-linked conjugate, the stability of which in the presence of thiols is uncertain. We have investigated the conjugation of an RGD peptide, glycine-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Unfortunately, we could not locate a commercial source of cysteinylglycine for this study and, hence, utilized the cysteine as a reasonable substitute. Although not explored here, pH of the cleaving medium is expected to significantly influence the cleavage rates by modulating the thiolate concentration in solution (i.e., dissociation of the thiol compounds); we found that SPDP-linked disulfide conjugates of an arginine-glycine-aspartic acid (RGD) peptide with a cationic polymer (polyethyleneimine) underwent cleavage that was accelerated at higher pH values, 25 consistent with the expected effect of the pH on the fractional dissociation. Finally, one must consider the possibility of cysteine causing alterations in BSA structure (i.e., denaturation) to be responsible for the reduced protein binding to HA.…”
Section: ϫPhsupporting
confidence: 79%
“…Unfortunately, we could not locate a commercial source of cysteinylglycine for this study and, hence, utilized the cysteine as a reasonable substitute. Although not explored here, pH of the cleaving medium is expected to significantly influence the cleavage rates by modulating the thiolate concentration in solution (i.e., dissociation of the thiol compounds); we found that SPDP-linked disulfide conjugates of an arginine-glycine-aspartic acid (RGD) peptide with a cationic polymer (polyethyleneimine) underwent cleavage that was accelerated at higher pH values, 25 consistent with the expected effect of the pH on the fractional dissociation. Finally, one must consider the possibility of cysteine causing alterations in BSA structure (i.e., denaturation) to be responsible for the reduced protein binding to HA.…”
Section: ϫPhsupporting
confidence: 79%
“…PEI-conjugates have been prepared, e.g. with epidermal growth factors, 97 monoclonal antibodies, 98 RGD peptides for integrin mediated endocytosis, 100,101 peptides for binding growth factor receptors, 102 sugars, and many more. The use of SPDP is highly efficient and enables the tuning of the functionalization degrees by simply varying the molar ratios.…”
Section: Pei-conjugatesmentioning
confidence: 99%
“…It was shown that thiols such as mercaptoethanol and cysteine at physiological concentrations cause a rapid cleavage of the ligand from the PEIs. 101 Alternatively, maleimides are versatile linkers for the binding of thiol containing ligands by formation of thioether bonds, as demonstrated for succinimidyl trans-4-(maleimidylmethyl) cyclohexane-1-carboxylate (SMCC, Scheme 5b), 102 N-(maleimidobutyryloxy)succinimide (GMBS) 103 and N-(maleimidoundecanoyloxy)sulfosuccinimide ester (sulfo-KMUS, Scheme 5c) 104 with very high yields for functionalization and a good control over the reaction. Sulfo-KMUS can also be used for the coupling of primary amines via thiolation of PEI using 2-iminothiolane and subsequent reaction of sulfo-KMUS activated amines with the thiolated PEI.…”
Section: Pei-conjugatesmentioning
confidence: 99%
“…The peptide contents were determined using established HPLC method. 32 Meanwhile, the mass fraction of coated HAp nanoparticles was quantitatively characterized using thermo gravimetric analysis (TGA) (Waltham, MA). The samples were heated from room temperature to 800 C with increment of 20 C/min in a nitrogen atmosphere at an airflow rate of 40 mL/min.…”
Section: Multifunctional Coatings and Characterization Of Plga-[asp-pmentioning
confidence: 99%